Urban landmarks and their relationships with place attachment - Ziaei, Sourena (2014)
Place is a physical location which is formed through individual’s relationship with physical environments, activities and meanings. In its essence, Place Attachment (PA) is a theory, which can describe the quality of the relationship between human and place. It is defined as the affective ties that people set up with particular settings, exactly where they desire to remain being along with as well as where they can experience safety and comfort. Based on the KL Structure Plan of 2020, rapid development has left the city of Kuala Lumpur rather lacking in its legibility and identity. It is claimed that people are more attached to activities in the city rather than the physical characteristics and natural elements of the places. Due to the ongoing issues on disharmony in the development which affects major landmarks, it is assumed that place attachment to the places is also decreasing. Attraction to landmark places can be affected by the weakening of place identity. Despite the fact that the significant roles of landmarks on people’s sense and attachment is mentioned by many scholars, there is still a gap in these researches about attachment to landmarks which act as external point-references to the observers that contribute to making a city legible. Previous studies mostly have focused on perception of landmark between different users. For example, Lynch (1960) studied on the five physical components that influence imageability. However, the study did not examine the psychological effects of experiencing such places. This study examines the psychological aspects of the place by examining place attachment, which provides a more comprehensive assessment on place. It focuses on the people’s level of attachment to different types of landmarks and examines their influences on two existing landmark places in Kuala Lumpur city. It is assumed that urban landmarks contribute to the people’s sense of attachment and the quality and types of engagement with the places they experience. This study seeks to identify the characteristics of the selected landmarks and the factors that strongly influenced place attachment. A questionnaire survey was conducted with 300 respondents who were engaged in Dataran Merdeka and Kuala Lumpur City Center Park (KLCC Park). These two places are important landmarks of Kuala Lumpur, which play influential roles in attracting both tourists and locals to the city. The study clarifies that both selected open space landmarks contain all four essential characteristics to prove place values to act as landmarks and discovers that there was a significant relationship between characteristics of the urban landmarks and the development of place attachment in the context. Additionally, in terms the influence on functional attachment, Singularity and Special Prominence found to be the most effective characteristics of landmarks while Singularity and Meaning are those ones whom affect emotional attachment. Moreover, individuals developed stronger emotional bonds to both selected landmarks in comparison to the functional ties while in KLCC Park the functional attachment was greater than the square and in contrast, Merdeka is where people are attached to more emotionally compare to the park. The findings will assist city authorities, planners and designers to provide people with landmarks, which are responsive to user’s need and therefore support continuous attachment either functionally or emotionally. These shall result in their persistent engagement with the places and increase in frequency of visit particularly to landmarks within tourism places in the metropolitan city of Kuala Lumpur.